Reading the Signs of the Times through a Hermeneutics of Recognition Gaudium et Spes and Its Meaning for a Learning Church - Faggioli, Massimo 1970- (2016)
The pastoral constitution Gaudium et Spes of Vatican II represents a significant shift for the church, not only ecclesiologically but also intellectually, with deep consequences for the culture of the church and especially for Catholic institutions of higher education. This change has clear implications for the core curriculum of a learning Catholic Church-and of every learning Catholic. In the "modern cosmopolitan culture" of the church of Vatican II, the liberal arts have a central place. The ability to make a judgment on "the signs of the times" requires a cultural awareness that is the opposite of utilitarianism. Care for the "common good" requires "core knowledge" because the world-as it is presented in Gaudium et Spes-is nontransparent, ambiguous, and ever changing. In this sense the pastoral constitution is an antipositivistic manifesto for humanization that needs to be rediscovered.
Keywords: Gaudium et Spes; Vatican II; core curriculum; Education; Humanization; Liberation; Recognition